Application of Supply Chain Finance in Indonesian Banking Sector for Anti-Money Laundering - Sjukri Karim, Atqkan; Mohamed, Nafsiah; Azmi Niaz Ahamd, Muhammad; Prabowo, Hendi Yogi (International Journal of Supply Chain Management, 2020)
Abstract- One good way to adopt a fresh perspective is by looking at how leading consumer business (CB) organizations efficiently move goods through their supply chains. Money laundering is the process by which large amount of illegally obtained money from drug trafficking, terrorist activity or other serious crimes, is given the appearance of having originated from the legitimate source. Money laundering is a risk faced by all banks because money laundering often use banking sector facilities to move, exchange or disguise illegal funds. This study aims to identify the effect of finacail supply chain on money laundering intention in the Indonesian banking sector. The design of this study used combination of quantitative and qualitative methods. Quantitative methods are carried out by surveys and in-depth interviews on qualitative methods. The results of this study indicate that financial supply chain system have a positive effect on money laundering intentions.